Post-democracy or De-democratisation? Some Reflections between History and Politics on the Contemporary Debate - Elia Zaru (Scienza & Politica, 2024)
This essay deals with the contemporary debate on the so-called crisis of democracy in light of the ideas of «post-democracy» and «de-democratization» and the link between this crisis and neoliberalism with respect to the relationship between politics, democracy, equality and collective action. The first paragraph is devoted to the lemma «postdemocracy» and traces its historical and theoretical roots to the semantic of «post». The second section shows how from a neoliberal perspective the crisis of democracy does not constitute a problem (as in the «post-democracy» perspective), but a solution to a problem, namely the «problem» of an «over-democratization» of society. In order to do so, this section reflects on the link between considerations expressed in the Report of the Trilateral Commission (1975) and the recent epistocratic political proposals. Finally, after a brief analysis of the criticism addressed to epistocracy, which are discussed in the third paragraph, the fourth one outlines some conclusions that reconnect the discourse on the crisis of democracy to the issues of equality and collective actions.